Español Español - Roessler Vergara, Pablo Ignacio; Soto Ramírez, Tomás; Cabieses, Báltica (Medicina Clínica y Social, 2021)
Introduction: Venezuelan immigrants residing in Chile have increased not only in quantity, but also in the vulnerability in which they migrate. Therefore, it becomes relevant to understand how they carried out one of the most promulgated care measures to COVID-19 propagation: compliance quarantine. Objective: Analyze which elements made it difficult to carry out quarantine in the Venezuelan population residing in Chile, since confinement is one of the most promulgated measures to protect the population from the spread of COVID-19. Methodology: We conducted an observational quantitative cross-sectional study based on an online survey on COVID-19 among international migrants living in Chile, carried out in April 2020, through a “snowball” sampling strategy (n=1,690 migrants). This secondary analysis is focused on Venezuelan participants (N=1,006), through descriptive, bivariate and multivariate regression analyses, with Raking adjustment to reduce self-selection bias. Results: The chances of non-compliance the quarantine recommendation are higher in those who have job ([OR=5,35, 95%IC [3,16-9,02]), in relation to those who do not; in those who not have a have a health plan ([OR=4,02, 95%IC [1,57-10,32]), and those who have public plan (Fonasa) ([OR=3,92, 95%IC [1,84-8,35]), in relation to people with private health insurance; in men ([OR=2,23, 95%IC [1,50-3,32]) than in women; and in those with a lower education level at a higher lever ([OR=1,74, 95%IC [11,50-3,32]). Conclusions: The association between not complying with quarantine and working conditions and type of health insurance, exposes the relevance of socioeconomic vulnerability in the opportunities to carry out public health care measures in the Venezuelan migrant population in Chile, such as the monitoring of confinement during a pandemic like COVID-19. This is important for health planning in future socio-health crises.